Resistência induzida por elicitores e proteção de videira contra míldio - Finger, Geísa (2015)
The grapevine is a fruit that has significant importance in the world economic sector and several factors may compromise its development and especially productivity, including pathogen attack. The disease known as downy mildew is caused by Plasmopara viticola and may cause serious damage to the crop if not controlled. Thus, the major way of controling the disease is associated with the use of fungicides, which causes risks to the environment and human health. The aim of this study was to evaluate the potential of biological agents and chitosan on controlling downy mildew throughthe induced resistance mechanism in grapevine cv. Cabernet Sauvignon. It was hypothesized that the biological agents Trichoderma spp. and Bacillus subtilis, as well as chitosan have the ability to affect directly the viability of P. viticola sporangia and to elicit defense responses in leaf cells of grapevine. Germination of sporangia was measured in vitro andexperiments in greenhouse were conducted, aimed at monitoring the progress of downy mildew on plants exposed to the products studied and, two days later, inoculated with P. viticola. In another experiment, in the absence of the pathogen, leaf tissue of grapevine plants exposed to the same products was collected for conducting biochemical and biological analysis, aiming to characterize the induction of resistance (IR) in plant cells. The activity of pathogenesis related proteins (PRPs) such as guaicol peroxidases, chitinases , β-1,3-glucanases , and polyphenoloxidases in leaves exposed to the products was determined, as well as the levels of total soluble phenols and lignin. Chitosan, but not the biological control agents, reduced the viability of sporangia of P. viticola. All products promoted protection, although not significant when compared to control plants. All studied products produced alterations in the production of PRPs and total phenols. Despite the sharp increase, but not significant, in the lignin content of leaves, small reduction in the area under the mildew progress curve was observed that can be attributed to mechanisms of resistance induction activated by the products studied through elicitor action.